Ultrasound-Guided Sciatic and Femoral Block in Patient with Recent Embolism Stroke Undergo Amputation Above the Knee - Propan Hanggada Satyamakti Mubarak (Journal of Anaesthesia and Pain, 2021)
Background: Patients undergoing amputation of the lower extremities usually have poor circulation and other comorbidities and, therefore, present a challenge to the anesthesiologist. The combination of sciatic and femoral nerve block is reported to be an effective anesthetic technique for patients undergoing knee surgery, and it is known to be an effective method of postoperative analgesia in patients undergoing major surgery on the subject's lower extremities.Case: A 70-year-old man with a recent embolism stroke, death of his limb on the right cruris region, and underwent an amputation above the knee. Preoperative physical examination showed GCS E4 V, motor aphasia M6, blood pressure 131/82 mmHg, pulse 114 bpm, RR 20 times/minute with bodyweight 70 kg, height 160 cm, SpO2 97%. There was cyanosis in the right cruric region with motor power of 1/5 1/5. The value of leukocytes 18,600/ul, platelets 309,000/ul, Prothrombin Time (PT) 15.8 seconds, Activated partial thromboplastin time (APTT) 25.9 seconds,  International normalized ratio (INR) 1,330, neutrophils 81.7%, lymphocytes 12.6%, creatinine 1.8 mg/dl, urea 137 mg /dl, blood sugar at the time 258 mg/dl, Cl 95 mmol/l.  This case report suggests that ultrasound-guided peripheral nerve blocks may be useful for major lower extremity surgery in patients with severe hemodynamic impairment.Conclusion: Perioperative management of embolism stroke patients undergoing above-knee amputation requires special attention in selecting anesthetics. Ultrasound-guided peripheral nerve blocks minimize patient hemodynamic changes and provide better postoperative pain control.